Sympathetic Ophthalmitis: A Case Presentation and Review of the Literature - Dilshad Laghari, Sadaf Ambreen, P. S. Mahar, Aimal Khan (Pakistan Journal of Ophthalmology, 2011)
Sympathetic Ophthalmitis (SO) is a rare, bilateral granulomatous uveitis occurring after perforating eye injury or ocular surgical procedure to one eye. The pathophysiology of this entity is not clearly understood but an autoimmune hypersensitivity reaction against exposed ocular antigens in the injured eye is believed to be responsible for this disease. In this article, we present a patient with clinical diagnosis of SO and review the literature.